Sufi Women, Embodiment, and The 'Self': Gender in Islamic Ritual - Rodrigues, Jamila (Taylor & Francis Group, 2023)
Cover -- Half Title -- Title Page -- Copyright Page -- Table of Contents -- Acknowledgements -- Introduction -- Chapter 1 The Salikun journey begins -- Chapter 2 From theory to practice -- Chapter 3 The inner Islam: An overview of Sufism and Sufi notions of the body -- Chapter 4 Dancing with God: Hadra as sacred dance and cultural embodiment -- Chapter 5 'De-code' hadra: Body movement analysis of the ritual practice -- Chapter 6 Symbolic embodied practice: The Sufi 'mystical body' and women's religious identity -- Chapter 7 'Let the bird fly' … somatic practice and hadra performance, the embodied experience -- Chapter 8 The salikun journey ends -- Bibliography -- Glossary of terms -- Index.